Understanding Homicide-Suicide - Fırat, Sunay; Erk, Mehmet Aykut; Dokgöz, Halis (The Bulletin of Legal Medicine, 2020)
The term ¨Homicide-Suicide¨ is described with an interpersonal violence where a perpetrator commits suicide after murders at least one victim. Mostly it has been thought that it is an act which is posterior to decision of suicide of the dominant family member. In various cases this situation is considered as a concern of the dominant member about leaving no-one behind. It has been considered that in those cases where an individual has suicided or has been killed perpetrators persuade the victims even if they aren’t willling to do it. By homicide-suicide’s very nature perpetrator and victim are deceased thus several sorts of information do not include sufficent nuance about the causes and dynamics of the event. In this paper, it is aimed that to examine fundamentals, prevalence and differences of homicide suicide and to provide a perspective about spesific traits of sub-types of the cases with the help of literature.The method of psychological autopsy, which is conducted in order to determine the psychological/psychiatric antecedents and risk factors of the cases, includes all kind of data collection and examination. Due to these reasons it is very important to profiling the individuals and to enlighten the causes of homicide-suicide with examinations and evaluations.Consequently, it has been thought that it would be very contributing to prepare a protocol for psychological autopsy and to support proffessions. Also it would be beneficial for risk prevention studies both indivudually and socially.
Keywords: Homicide-suicide; interpersonal violence; psychological autopsy; ppsychological antecedents